The Asian Eye: Anthropometric Eye Measurements of Attractiveness in Young East Asian Women. Issue 5 (22nd August 2022) - Patel, Anooj A.; Wan, Rou; Garg, Stuti; Ullrich, Peter; Vaca, Elbert E.; Alghoul, Mohammed S.; Ellis, Marco; Galiano, Robert D.
Abstract : Background: Because of the high volume of Asian eyelid operations performed and the complexity of the Asian eye, there is a need to define exactly what anthropometric measurements determine attractiveness. Methods: Eye photographs of young East Asian women were collected from publicly available sources online. Photographs were evaluated on a Likert scale ranging from 1 to 5 for attractiveness. Thirty-seven anthropometric measurements were collected using ImageJ from the most attractive and least attractive eyes to discover which features play the most important role in attractiveness. Results: A total of 322 right eye photographs were evaluated for attractiveness. Sixty-six eyes received a median score of greater than or equal to 4.0 and were included in the attractive cohort. Forty-three eyes received a score of less than or equal to 2.0 and were included in the unattractive cohort. The superior brow peak was more lateralized compared to the upper lid crease and upper lash line peaks in attractive eyes. A greater palpebral aperture height–to–upper lid show ratio was found to be more associated with attractive eyes than with unattractive eyes. At the midpupillary line, the ratio was on average 1.58 ± 0.32 in attractive eyes and 1.22 ± 0.43 in unattractive eyes ( p < 0.001). Eyes with convergence of the upper lid crease with the upper lash line were more likely to be deemed unattractive ( p < 0.001). Conclusions: East Asian eyes have specific anthropometric measurements that are more associated with attractiveness. These ideal measurements are different from those in Caucasians, suggesting ethnic variability in features defining attractiveness and a need to tailor surgical care appropriately.